Justice for Palestine: A Call to Action from Indigenous & Women of Color Feminists - The People's Forum NYC (2021)
We come together on the 10th anniversary of our last day in Palestine, hundreds of presentations, articles, panels, and interventions later, to offer our Report Card reaffirming the relevance and urgency of re-telling stories of apartheid, ethnic cleansing, and settler colonialism and of Palestinian steadfastness, resistance and resilience. SPEAKERS: Dr. Angela Davis Dr. Anna Guevarra Dr. Barbara Ransby Dr. Beverly Guy-Sheftall Dr. Chandra Talpade Mohanty Dr. Gina Dent Dr. G. Melissa Garcia Dr. Rabab Abdulhadi Dr. Waziyatawin Co-sponsored by Arab and Muslim Ethnicities and Diaspora Studies
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; asie; cours; discipline; féminisme autochtone; féminisme décolonial; féminisme islamique; féminismes noirs; génocide; histoire et politique; militance; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; études arabes; études décoloniales

Le féminisme décolonial en Abya Yala - Curiel, Ochy; De Roo, Priscilla (Multitudes, 2021)
Les rapports sociaux de race, de genre, de sexe sont inextricablement mêlés : telle est une idée centrale du féminisme décolonial tel qu’il se déploie depuis Abya Yala, du nom que le peuple kuna donnait au continent américain. L’article situe l’importance de renommer les femmes et féministes d’origine autochtone, une manière de défaire les discours coloniaux (parfois tenus par des universitaires féministes) sur les pratiques de genre avant la colonialité/modernité. Ochy Curiel illustre cette idée à partir de l’expérience du GLEFAS (Groupe latino-américain de formation et d’action féministe) : le décolonial n’y est pas seulement une critique du savoir académique, il est profondément ancré dans des pratiques autogestionnaires de luttes anticapitalistes, dans le lesbianisme politique, dans la rue, dans les associations, dans les organisations communautaires.
Keywords: amériques; anthropologie; anthropologie sociale; approches et analyses; cours; discipline; féminisme autochtone; féminisme décolonial; histoire et politique; intersectionnalité; lesbianisme; militance; pol4212; premier cycle; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Before the “Ecologically Noble Savage”: Gendered representations of Amazonia in the global media in the 1970s - Sarzynski, Sarah (Latin American Perspectives, 2021)
An analysis of media representations of the Amazon and indigenous peoples reveals how media producers and filmmakers foregrounded discourses naturalizing gendered and racialized differences that distinguished the Amazon from the West in the 1970s, a decade during which the Brazilian military dictatorship promoted development projects in Amazonia. These representations often sexualized indigenous peoples and the Amazon itself, portraying them as primitive, cannibal savages, animals or part of nature, or victims of exploitation. The “Othering” of the Amazon and Amazonians was further elaborated through a discourse of binary oppositions that portrayed Western white men as explorers and exploiters who dominated the screen, scripts, studies, and development projects even if they were doomed to fail. By relying on a symbolic system of difference, global media coverage and films about Amazonia in the 1970s were complicit in legitimizing authoritarian decrees promoting large-scale development that depicted indigenous peoples and the environment as obstacles. Un análisis de las representaciones mediáticas de la Amazonía y sus pueblos indígenas revela cómo, en la década de 1970, productores y cineastas mediáticos resaltaron discursos que naturalizaron las diferencias de género y racializadas con las que se distinguían a la Amazonía del Occidente en una época durante la cual la dictadura militar brasileña promovió proyectos de desarrollo en la región. Dichas representaciones a menudo sexualizaban a los pueblos indígenas y a la Amazonía misma, retratándolos como primitivos, caníbales salvajes, animales o elementos naturales, o víctimas de explotación. La “otredad” de la Amazonía y los amazónicos se elaboró a través de un discurso de oposiciones binarias que retrataba a los hombres blancos occidentales como exploradores y explotadores que dominaban la pantalla, los guiones, los estudios y los proyectos de desarrollo, incluso si estos estaban condenados al fracaso. Al confiar en un sistema simbólico de diferencia basado en oposiciones binarias y estereotipos, la cobertura mediática global y las películas sobre la Amazonía en la década de 1970 fungieron como cómplices en la legitimación de los tipos de proyectos y políticas llevados a cabo en la región. © 2021 Latin American Perspectives.
Keywords: amazonie; amériques; approches et analyses; brésil; discipline; domination blanche; domination masculine; histoire; histoire et politique; médias; peuples autochtones; projet charge mentale; racisme; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; violences coloniales; violences racistes; violences sexistes

Decolonizing methodologies: research and indigenous peoples - Smith, Linda Tuhiwai (Zed Books, 2021)
''To the colonized, the term 'research' is conflated with European colonialism; the ways in which academic research has been implicated in the throes of imperialism remains a painful memory.This essential volume explores intersections of imperialism and research - specifically, the ways in which imperialism is embedded in disciplines of knowledge and tradition as 'regimes of truth.' Concepts such as 'discovery' and 'claiming' are discussed and an argument presented that the decolonization of research methods will help to reclaim control over indigenous ways of knowing and being.Now in its eagerly awaited third edition, this bestselling book includes a co-written introduction features contributions from indigenous scholars on the book's continued relevance to current research. It also features a chapter with twenty-five indigenous projects and a collection of poetry.''-- Site de l'éditeur.
Keywords: approches et analyses; cours; discipline; féminisme autochtone; féminisme décolonial; histoire et politique; militance; méthodologie; méthodologie autochtone; pol4105; premier cycle; pédagogie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; études autochtones

Guérison Collective Healing - Yuen, Felice; Gabriel, Wanda; Fast, Elizabeth (Guérison Collective Healing, 2021)
Aborder les expériences des femmes autochtones dans les prisons provinciales du Québec Vers une guérison collective Addressing the experiences of Indigenous women in Quebec’s provincial prison Towards Collective Healing
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; canada; communauté; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; militance; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système carcéral; système colonial; systèmes d'oppressions; thématiques; travail social; violences